Photodynamic therapy against onychomycosis - Juliana P. Lyon; Leonardo M. Moreira (Termedia Publishing House, 2021)
Photodynamic therapy (PDT) has been considered a suitable alternative for the treatment of onychomycosis, especially for patients who cannot receive oral antifungal agents or with recurrent infections of the nail. This manuscript intends to analyse the published articles that report the use of PDT in vivo for the treatment of onychomycosis. A PubMed search was conducted with the key words photodynamic therapy and onychomycosis, according to the PRISMA guidelines. Only in vivo studies with clinical and laboratorial evaluations were included in the present study. Fourteen manuscripts were evaluated, according to the inclusion criteria defined, comprising a ten years' period of studies. The manuscripts differed widely regarding the number of patients involved, photosensitizer employed, protocol details, time of follow up and outcomes. Different parameters should be compared in order to define the best therapeutic approach and to contribute to a more widespread use of PDT in onychomycosis.